The Empties Heroes: Sebuah Referensi Misi Ekofeminis Sebagai Upaya Strategis ‘Perempuan-Gereja’ Berperan Bagi Pemeliharaan Bumi - Udang , Frety Cassia (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2023)
The empties heroes aims to embody conceptual transformation into impactful actions that can be carried out by church’s women. Therefore, in this research, the respondents are church’s women who are members of the Categorical Service Unit of Wanita/Kaum Ibu GMIM Pinaesaan GPI Manado Congregation. The determination of respondents was based on a purposive sampling technique. This research uses a qualitative descriptive and phenomenological approach to examine, describe and then formulate the discourse of the empties heroes as an ecofeminist mission movement. Based on this research, it was found that all respondents were active beauty product users and used the products until they were finished. The empty heroes movement can be accommodated as a movement or effort with a concrete ecofeminist mission among church’s women GMIM Pinaesaan GPI Manado Congregation.